Environmental Cues Contribute to Dynamic Plasma Membrane Organization of Nanodomains Containing Flotillin-1 and Hypersensitive Induced Reaction-1 Proteins in Arabidopsis thaliana - Xu, Changwen; Abbas, Sammar; Qian, Hongping; Yu, Meng; Zhang, Xi; Li, Xiaojuan; Cui, Yaning; Lin, Jinxing (Frontiers in Plant Science, 2022)
Plasma membranes are heterogeneous and contain multiple functional nanodomains. Although several signaling proteins have been shown to function by moving into or out of nanodomains, little is known regarding the effects of environmental cues on nanodomain organization. In this study, we investigated the heterogeneity and organization of distinct nanodomains, including those containing Arabidopsis thaliana flotillin-1 (AtFlot1) and hypersensitive induced reaction-1 proteins (AtHIR1), in response to biotic and abiotic stress. Variable-angle total internal reflection fluorescence microscopy coupled with single-particle tracking (SPT) revealed that AtFlot1 and AtHIR1 exhibit different lateral dynamics and inhabit different types of nanodomains. Furthermore, via SPT and fluorescence correlation spectroscopy, we observed lower density and intensity of AtFlot1 fluorescence in the plasma membrane after biotic stress. In contrast, the density and intensity of signal indicating AtHIR1 markedly increased in response to biotic stress. In response to abiotic stress, the density and intensity of both AtFlot1 and AtHIR1 signals decreased significantly. Importantly, SPT coupled with fluorescence recovery after photobleaching revealed that biotic and abiotic stress can regulate the dynamics of AtFlot1; however, only the abiotic stress can regulate AtHIR1 dynamics. Taken together, these findings suggest that a plethora of highly distinct nanodomains coexist in the plasma membrane (PM) and that different nanodomains may perform distinct functions in response to biotic and abiotic stresses. These phenomena may be explained by the spatial clustering of plasma membrane proteins with their associated signaling components within dedicated PM nanodomains.